Sense of Coherence dan Career Adaptability pada Karyawan di Awal Karir - Anggraini, Dewi; Pratiwi, Marisya; Juniarly, Amalia; Fitri Anjani, Manisa; Setio Nugroho, Pamariko (Universitas Muhammadiyah Metro, 2023)
Career adaptability is essential for employees at the beginning of their careers because they are required to develop and maintain their job status quickly. This enables them to plan their development, opportunities, and career transitions in the 21st century, characterized by numerous rapid changes. Career adaptability is the capacity of individuals to respond more quickly to stress. A sense of coherence, determined by how an individual copes with their environmental circumstances, is one of the stress-resilient positive psychological characteristics. This study explores the association between early-career employees' feelings of coherence and career adaptability. This study's sample comprised 163 employees in the early stages of their careers, aged 18 to 35. This study demonstrates a correlation between a sense of coherence and career adaptability among early-career employees.